GravCPA: Controller Placement Algorithm Based on Traffic Gravitation in SDN - Chenhui Wang; Hong Ni; Lei Liu (Journal of Control Science and Engineering)
Software-defined network separates the control plane and the data plane, making the network more flexible. With the expansion of the network scale, one centralized controller cannot meet the latency needs of large-scale networks. Therefore, it is necessary to use multicontroller architecture, which has some problems with the controller placement. In this article, we take both the average latency and the worst latency between switch and controller into consideration and make a multi-objective optimization model. An improved label propagation algorithm based on traffic gravitation is proposed to solve the subdomain division problem, and a heuristic method is for subdomain controller placement. The simulation experiments show the effectiveness of the proposed algorithm and the time complexity guarantee for large-scale networks.